Is Indonesian Islam Different? Islam in Indonesia in a Comparative International Perspective - Testriono, Testriono (Studia Islamika, 2011)
Center for the Study of Islam and Society (Pusat Pengkajian Islam dan Masyarakat, PPIM) of the State Islamic University (UIN) Syarif Hidayatullah Jakarta in cooperation with Leiden University, the Netherlands, the Embassy of the Kingdom of the Netherlands (Ministry of Foreign Affairs, the Netherlands), and the Ministry of Religious Affairs, Indonesia, held an international conference called: ‘Is Indonesian Islam Different? Islam in Indonesia in a Comparative International Perspective’ on January 24-26, 2011 in Bogor, West Java.DOI: 10.15408/sdi.v18i1.445